2015
DOI: 10.18052/www.scipress.com/ilcpa.56.120
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured ZrO<sub>2</sub> Thin Films Deposited by Spray Pyrolysis Techniques for Ammonia Gas Sensing Application

Abstract: ABSTRACT. The spray pyrolysis deposition technique has number of advantages to produce advance nanostructured oxide films. The film surface morphology and structure depends on the precursor and doping solution and solvents used with their optimized parameters. The surface to volume ratio is achieved is beneficial to gas sensing. Therefore in this paper we report the nanostructured ZrO 2 thin films was prepared using spray pyrolysis technique for ammonia gas sensing. There is various precursors such as Zirconiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…of Gd 3+ , only cubic ZrO 2 was obtained and the optical performance exhibited an intense UV emission up to 2.5% of Gd 3+ , whereas the red emission decreases with increasing Gd 3+ concentration. Stabilized zirconia can be obtained by several methods such as sol-gel [29][30][31][32][33], spray pyrolysis [34], co-precipitation [22,35], hydrothermal/solvothermal [8,20,36], electrochemical deposition [37] and combustion [23,26,38]. Nevertheless, most of these methods shows disadvantages related to the employed of high reaction temperatures, expensive processing techniques and long reaction times.…”
Section: Introductionmentioning
confidence: 99%
“…of Gd 3+ , only cubic ZrO 2 was obtained and the optical performance exhibited an intense UV emission up to 2.5% of Gd 3+ , whereas the red emission decreases with increasing Gd 3+ concentration. Stabilized zirconia can be obtained by several methods such as sol-gel [29][30][31][32][33], spray pyrolysis [34], co-precipitation [22,35], hydrothermal/solvothermal [8,20,36], electrochemical deposition [37] and combustion [23,26,38]. Nevertheless, most of these methods shows disadvantages related to the employed of high reaction temperatures, expensive processing techniques and long reaction times.…”
Section: Introductionmentioning
confidence: 99%
“…The observed band gaps are 4.67 and 4.8 eV for thick and thin film respectively. It is found that increase in band gap may be due to decrease in grain size [17][18][19][20][21][22][23]. Table 2 concludes that thin films are suitable for different application since it provides significant properties of thin films.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…At higher temperature that is [2300°C it has cubic structure, at intermediate temperature it has tetragonal structure and at low temperature that is\1100°C, it exists in monoclinic structure [15]. Recently, zirconia has created a great attention due to its supreme technological significance, because of its high refractive index, high thermal expansion coefficient, excellent oxygen ion conductivity, high dielectric constant, high corrosion resistance, high chemical stability, great toughness, microbial resistance [16][17][18][19][20][21][22][23][24], etc., which makes this SMO to emanate as an attractive material for massive functions in photonics, gas sensors, bio-sensor, thermal barrier coatings, fuel cells, dental medicine, buffer layer in high T c superconductors and so on [25][26][27][28][29][30][31]. The REDOX movement and the quality of high ionic exchange drive the metal as useful as catalyst [18].…”
Section: Introductionmentioning
confidence: 99%